In-House Validation of Rapid Detection PCRs for Bacterial Pathogens Causing Infant Diarrhea - Londero, Alejandra (2017)
In Argentina, conventional culture methods for the isolation of diarrheal bacteria continue to be the most widely used form of diagnosis in many clinical laboratories. In this work we validated 11 in-house real-time polymerasechain reactions (PCRs) assays for the specific and rapid detection of Salmonella spp., Shigella spp., enteroinvasive E. coli, enteropathogenic E. coli, enterotoxigenic E. coli, Shiga toxin-producing E. coli, E. coli O157, Cronobacter sakazakii, Campylobacter jejuni, Campylobacter coli, Vibrio cholera and Clostridium difficile. The sensitivity of the assays was less than 100 CFU/ml for all the studied pathogens; selectivity and specificity were 100% in all cases and robustness was optimal. These PCR methods could be used to accurately detect the main bacterial causes of infant gastroenteritis.